Developing Facilities Management (FM) competencies for Malaysia: reference from international practice - Kamaruzzaman, Syahrul Nizam; Myeda, Nik Elyna; Zawawi, Emma; Ramli, Rozita Mohamed; Pitt, Michael (Emerald, 2018)
Purpose: The purpose of this paper is to investigate the significance of facilities management (FM) competency levels from three different stages, namely, strategic, tactical and operational levels, to propose a set of FM competencies for an enhanced FM industry in Malaysia. Design/methodology/approach: The overall focus for this paper is to discuss on the area for each level of competencies for asset and facilities management (AFM). This is done through a questionnaire survey focusing on the competency areas posed by FM companies in Malaysia and a comparison review of all FM levels as outlined by the international professional bodies, namely, International Facility Management Association, British Institute of Facilities Management and Royal Institute of Chartered Surveyors. This paper also looks at formulating a holistic framework for an effective AFM for the benefit of FM industry in general and Malaysian FM industry specifically. Findings: The findings indicate that among the significant factors for the respective strategic, tactical and operational practice of FM are strategic: managing change, benchmarking and strategic facilities planning; tactical: risk management, emergency preparedness, FM technology, service-level agreement and supply management; and operational: space planning and management. This study also proposes a set of holistic FM competency areas which can be implemented by the FM industry in Malaysia. Originality/value: This research sets a baseline for a set of FM competencies, an area of FM which has not been regulated in the FM practice in Malaysia.